Options for the 2024 Spending Review and beyond - Bee Boileau; Max Warner; Ben Zaranko (Institute for Fiscal Studies (IFS), 2024)
We examine the challenges facing public services and the Chancellor's public spending options at the forthcoming Budget and Spending Reviews.
Keywords: 330; Government finances and spending; Government spending; Public finance; Public sector